Dynamical Study of An SIR Epidemic Model With Nonlinear Incidence Rate and Regress of Treatment - Majeed, Saba Noori (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this research, dynamical study of an SIR epidemical model with nonlinear direct incidence rate (Beddington-De Angelis ) type, and regress of treatment investigated .An analytical study to the model shows that there are two equilibrium points appear, the discussed successfully with sufficient condition, the existence of local bifurcation and Hopf bifurcation was analyzed, finally numerical simulations are done to explain the analytic studies.